Gambaran Karakteristik Penderita Fraktur Maksilofasial di Rumah Sakit Umum Haji Medan Tahun 2022-2024 - Febrini, Dewi; Estetika, Wa Ode Tri Exis; Henny, Henny (Syntax Literate, 2025)
Maxillofacial fractures are among the most serious injuries involving facial bones and are often caused by trauma, particularly traffic accidents. This condition not only affects the aesthetic and physiological functions but also has a significant impact on the patient’s quality of life. The high incidence of maxillofacial fractures has become an important concern in the fields of dentistry and oral and maxillofacial surgery. This study aimed to describe the characteristics of patients with maxillofacial fractures at Haji General Hospital Medan in 2022–2024, including the number of cases, age distribution, gender, causes of fractures, and types of fractures. This research employed a descriptive design with a retrospective approach. Data were obtained from the medical records of patients diagnosed with maxillofacial fractures who were treated at Haji General Hospital Medan during the 2022–2024 period. A total of 62 patients who met the inclusion criteria were included as research samples. Data were analyzed univariately in the form of frequency and percentage distributions, and presented in tables and bar charts. The results showed that the number of maxillofacial fracture cases increased each year, with 16 cases (25.8%) in 2022, 20 cases (32.3%) in 2023, and 26 cases (41.9%) in 2024. Based on age, the highest number of cases occurred in the 21–30 years age group (33.9%), followed by the 11–20 years group (30.6%). Based on gender, males experienced more maxillofacial fractures (46 cases, 74.2%) compared to females (16 cases, 25.8%). The main cause of fractures was traffic accidents (58.1%), followed by falls (17.7%). The most common types of fractures were maxillary fractures (41.2%) and zygomatic fractures (40.5%), followed by mandibular (6.9%), frontal and nasal (3.8% each), naso-orbito-ethmoidal (NOE) fractures (2.3%), and orbital fractures (1.5%). In conclusion, maxillofacial fractures at Haji General Hospital Medan in 2022–2024 were predominantly found in male patients of productive age (21–30 years), mainly caused by traffic accidents, with the most frequent fracture types being maxillary and zygomatic fractures. It is recommended that the public increase awareness and safety measures, especially while driving, including the use of protective equipment. Health institutions should strengthen educational programs on facial trauma prevention. Patients are advised to seek immediate medical attention to prevent complications. Further research is suggested to analyze more specific risk factors and evaluate post-treatment clinical outcomes.